Realizing a Child Friendly School Through Anti-Bullying and Environmentally Friendly Strategies at Tk Aisyiyah Bustanul Athfal III Candi: Mewujudkan Sekolah Ramah Anak Melalui Strategi Anti-Bullying Dan Ramah Lingkungan Di Tk Aisyiyah Bustanul Athfal III Candi (Indonesian Journal of Cultural and Community Development, 2024)
In order to move towards better education, a new initiative has emerged to create a safe and comfortable school environment for all children. The goal of this service is to create a safe and comfortable school environment for children through anti-bullying strategies and clean and green environmental efforts. The methods used include teaching students about bullying prevention, as well as school greening and cleaning programs. The expected results are increased awareness of bullying, reduced incidents of violence in schools and the creation of a beautiful school environment. The outputs of this service include anti-bullying educational videos, articles in online media and books that invite all educators to do the same activities, and through this program it is hoped that a generation will be created that is intelligent, has strong character and cares about the environment.